2004
DOI: 10.1103/physreva.70.040702
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron recapture as a tool for the spectroscopy of ionic Rydberg states

Abstract: We use recapture of near-threshold photoelectrons by postcollision interaction with Auger electrons as an effective method for population of the high-Rydberg states of subvalence ionized Ne ions. The subsequent intermultiplet Auger transitions are detected by high-resolution electron spectrometry. The series of transitions 2p 4 ͑ 1 D͒np 2 D , 2 F → 2p 4 3 P up to n = 20 are observed and identified with the help of multiconfiguration Dirac-Fock ab initio calculations.Spectroscopic data on atomic ions are requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Examples of such cascades have been discussed in previous sections. In recent paper by De Fanis et al (2004b), a method was suggested for populating effectively a large number of highly excited Rydberg ionic states. The cascade decay of these states produces a rich spectrum of Auger transition series converging to various levels of the doubly charged ion.…”
Section: Auger Cascades Following the Pci Induced Electron Recapture mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of such cascades have been discussed in previous sections. In recent paper by De Fanis et al (2004b), a method was suggested for populating effectively a large number of highly excited Rydberg ionic states. The cascade decay of these states produces a rich spectrum of Auger transition series converging to various levels of the doubly charged ion.…”
Section: Auger Cascades Following the Pci Induced Electron Recapture mentioning
confidence: 99%
“…Another approach for measuring the angular anisotropy of the emitted electrons was used in the experiments on the resonant Auger and second-step Auger processes in Ne 1s photoexcitation De Fanis et al, 2004bYoshida et al, 2005;Kitajima et al, 2006). These measurements were carried out using the high-resolution electron spectroscopy end-station of the soft X-ray photochemistry beam-line 27SU (Ohashi et al, 2001b) at SPring-8, the third generation SR source in Japan.…”
Section: Angle Resolved Auger Electron Spectroscopymentioning
confidence: 99%
“…Another large group of applications of the Ratip code concerns the (Auger) electron emission from inner-shell excited or ionized atoms [35][36][37][38][39] as well as the coherence transfer in Auger cascades. For the 2 p → 4s resonantly excited argon [40], for example, we were able to show by means of systematically enlarged wave function expansions that the initial and final-state configuration interactions can be taken into account to a large extent and bring the energy and intensity distributions into much better agreement with experiment [41].…”
Section: Overview To the Ratip Programmentioning
confidence: 99%
“…number of different experimental techniques [1][2][3][4][5][6][7][8][9] and by theory [10], and is well understood today. An important topic of early studies on Ne satellites was the distinction between different satellite production mechanisms [3].…”
mentioning
confidence: 99%